2016
DOI: 10.1177/0267659115627690
|View full text |Cite
|
Sign up to set email alerts
|

Angina severity predicts worse sleep quality after coronary artery bypass grafting

Abstract: The severity of angina pectoris in the preoperative period is independently associated with worse sleep quality after elective isolated coronary artery bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
0
16
1
1
Order By: Relevance
“…Severe preoperative coronary artery disease is also associated with worse sleep quality after surgery. In a small sample size study of Yilmaz et al [ 12 ], 52 patients undergoing coronary artery bypass graft surgery were assessed for postoperative sleep quality with Pittsburgh Sleep Quality Index. The results showed that patients with preoperative myocardial infarction had significantly worse sleep quality after surgery, and higher preoperative angina score was an independent predictor of poor sleep quality after surgery.…”
Section: Factors Associated With Postoperative Sleep Disturbancementioning
confidence: 99%
“…Severe preoperative coronary artery disease is also associated with worse sleep quality after surgery. In a small sample size study of Yilmaz et al [ 12 ], 52 patients undergoing coronary artery bypass graft surgery were assessed for postoperative sleep quality with Pittsburgh Sleep Quality Index. The results showed that patients with preoperative myocardial infarction had significantly worse sleep quality after surgery, and higher preoperative angina score was an independent predictor of poor sleep quality after surgery.…”
Section: Factors Associated With Postoperative Sleep Disturbancementioning
confidence: 99%
“…Regarding the main results of the articles included in the IR, they identified that patients with recent AMI had worse quality and quantity of sleep ( 11 , 24 , 32 ) and that a high angina score and length of stay in intensive care unit were predictors of poor sleep quality ( 24 ) . They also pointed out that during the hospitalization more than one third of the ACS patients had insomnia ( 29 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Canadians with high angina scores had a 3.27-fold higher chance of poor sleep quality. (26) In addition, a cohort pointed out that individuals with short sleep duration or poor sleep quality are more likely to develop cardiovascular disease (angina: 1.62% in the Netherlands, 8.11% Suriname in South Asia, 5.4% in Africa, 5.14% in Ghanaians, 10.1% in Turkey and 7.35% in Morocco, as well as intermittent claudication and myocardial infarction), among other findings that accompanied other health-disease situations such as obesity, hormonal changes and stresses, identified as risk factors for irregular sleep. (27) In the psychic dimension, the association found in this study has been identified as a risk factor for changes in sleep patterns.…”
Section: Discussionmentioning
confidence: 99%